Thermally conductive compositions for high temperature applications
Patent Information
- Application Number
- JP2024552312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-13
AI Technical Summary
【0005】 本発明により、従来のアルカンワックスは、高温安定性を示す二元機能相変化成分によって全部又は一部置換されてよく、それによって、二元機能相変化成分が使用される熱伝導インターフェイス材料に高温安定性が付与される。二元機能相変化成分は、融点温度が40~85℃の二次酸化防止剤を包含する。
Smart Images

Figure 2025506994000001 
Figure 2025506994000002 
Figure 2025506994000003
Abstract
Description
[Technical field]
[0001] The present invention relates generally to thermally conductive compositions, and more particularly to phase change thermally conductive compositions that are stable at high temperatures and limit performance degradation over time. [Background technology]
[0002] Thermally conductive materials are widely used, for example, as interfaces between heat-generating electronic components and heat sinks, allowing the transfer of excess thermal energy from the electronic components to the thermally coupled heat sink. Numerous designs and materials have been implemented for such thermal interfaces, with best performance achieved when gaps between the thermal interface and the respective heat transfer surfaces are substantially avoided to promote conductive heat transfer from the electronic components to the heat sink. Thus, it is preferred that the thermal interface material mechanically conform to the somewhat uneven heat transfer surfaces of the respective components. Moreover, it is preferred that the thermal interface material be useful for an extended lifetime at high temperature operation.
[0003] Electronic components such as semiconductors, microprocessors, resistors, and circuit boards generate significant amounts of heat that must be removed for the devices to function properly. High performance computing and communications applications generate significant heat, requiring thermal interface materials with very low thermal impedance to maximize heat transfer from sensitive electronic components. One conventional approach to providing a low impedance interface is temperature activated phase change materials. When the operating heat of the electronic components raises the temperature in the system above the softening or melting point of the phase change component of the thermal interface material, the viscosity of the interface is significantly reduced, improving conformance to the heat transfer surface and improving the efficiency of heat transfer to the electronic components. Phase change components in thermal interface materials are typically composed of alkane waxes, such as natural waxes, synthetic waxes, and petroleum-based waxes. Paraffin wax is often used as a phase change component because it has a melting point temperature in the range of approximately 40°C to 120°C. However, paraffin wax and other conventional phase change components degrade at the high temperatures encountered in high performance electronic devices. Degradation often includes drying and cracking after extended use at high temperatures, adversely affecting thermal performance.
[0004] It is therefore an objective to increase the high temperature stability of phase change thermally conductive compositions. Summary of the Invention [Means for solving the problem]
[0005] In accordance with the present invention, conventional alkane waxes may be replaced in whole or in part with a dual-functional phase change component that exhibits high temperature stability, thereby imparting high temperature stability to the thermally conductive interface material in which it is employed. The dual-functional phase change component includes a secondary antioxidant having a melting point temperature of 40-85°C.
[0006] In one embodiment, the thermally conductive composition includes a non-silicone resin, a primary antioxidant, and a secondary antioxidant that is compatible with the primary antioxidant and is present in the composition at a concentration of 20-50% by weight of the weight of the non-silicone resin. The secondary antioxidant is present in the composition at 95-99 parts by weight of the secondary antioxidant and 1-5 parts by weight of the primary antioxidant. The secondary antioxidant has a melting point temperature of 40-85° C. The thermally conductive composition further includes a thermally conductive particulate filler, the composition exhibiting a thermal conductivity of at least 1 W / m·K and less than 20% weight loss after 1000 hours at 175° C.
[0007] The thermally conductive composition may include 0.5 to 20% by weight of a non-silicone resin. In some embodiments, the thermally conductive composition may include 0.5 to 5% by weight of a non-silicone resin. The non-silicone resin may include a pressure sensitive adhesive. The non-silicone resin may include a polyamide.
[0008] In some embodiments, the secondary antioxidant may be thiol-based. In some embodiments, the secondary antioxidant may include didodecyl 3,3'-thiodipropionate. In some embodiments, the melting point temperature of the secondary antioxidant may be 50-60°C.
[0009] In some embodiments, the composition may include a hydrocarbon wax having a melting point temperature of from 40 to 120° C. In other embodiments, the composition may be substantially free of wax components.
[0010] In some embodiments, the thermally conductive particulate filler is selected from aluminum, aluminum nitride, aluminum-silica alloy, zinc oxide, and combinations thereof. The thermally conductive particulate filler has an average particle size (d 50 In some embodiments, the thermally conductive particulate filler comprises 70-95% by weight of the composition.
[0011] The thermally conductive composition may include a plasticizer. In some embodiments, the plasticizer includes trimellitate. In some embodiments, the trimellitate plasticizer is present in the composition at a concentration of 0.5-20% by weight of the composition. In some embodiments, the trimellitate plasticizer is present in the composition at a concentration of 0.5-5% by weight of the composition.
[0012] The thermally conductive composition may include a wetting agent. In some embodiments, the thermally conductive composition may include 0.1 to 1.5 wt % of a wetting agent.
[0013] The thermally conductive composition may further include an antioxidant different from the primary antioxidant and the secondary antioxidant. In some embodiments, the thermally conductive composition may include a sterically hindered phenolic antioxidant different from the primary antioxidant and the secondary antioxidant. In some embodiments, the thermally conductive composition may include 0.1 to 1.5 wt % of a sterically hindered phenolic antioxidant different from the primary antioxidant and the secondary antioxidant.
[0014] The thermally conductive composition may include a metal passivating antioxidant that is different from the primary and secondary antioxidants. In some embodiments, the thermally conductive composition may include 0.1 to 1.5 wt. % of a metal passivating antioxidant that is different from the primary and secondary antioxidants.
[0015] The thermally conductive printable composition includes a non-silicone resin, a primary antioxidant, a thiol-based secondary antioxidant, a thermally conductive particulate filler, and a solvent compatible with the remaining components of the composition. The thiol-based secondary antioxidant is compatible with the primary antioxidant and is present in the composition at a concentration of 20-50% by weight of the non-silicone resin. The secondary antioxidant may be present in the composition in a ratio of 95-99 parts by weight of the secondary antioxidant to 1-5 parts by weight of the primary antioxidant. The secondary antioxidant may have a melting point temperature of 40-85°C. The thermally conductive particulate filler may be present at 50-98% by weight of the composition, and the composition exhibits a thermal conductivity of at least 1 W / m·K and a weight loss of less than 20% after 1000 hours at 175°C. The composition dissolved in the solvent can be printed onto a substrate and dried to form a thermal interface material in thermal contact with the substrate. The composition can be printed onto the substrate by known printing techniques such as inkjet printing, extrusion through a die, three-dimensional printing, and the like. In some embodiments, the solvent may be selected from ethyl acetate and ethylhexyl acetate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Thermally conductive compositions and articles made from such compositions are disclosed. The articles can be used as thermal interfaces between heat generating components and heat dissipation devices.
[0017] In an embodiment, the electronic package includes a substrate and one or more electronic components secured to the substrate. The electronic package further includes a heat sink, such as a heat sink, and a thermal interface disposed in a thermal path between the electronic component and the heat sink. The electronic package is configured to dissipate thermal energy generated by the electronic component by providing a high thermal conductivity path from the electronic component to a heat absorbing fluid medium in contact with the heat sink. In a typical application, the fluid medium is a gas, such as air, which is moved by an air moving device to absorb thermal energy from the heat sink. The electronic package is useful in various electronic applications, such as data processors, data memories, communication boards, antennas, and the like. Such devices may be utilized in computing devices, communication devices, and their peripherals. In a particular example, the electronic package may be employed to support various functions of a cellular communication device.
[0018] In addition to being a support for electronic components, the substrate may serve one or more of a variety of functions. The substrate may be, for example, a circuit board, such as a printed circuit board, with conductive traces on a mounting surface for electrically connecting the electronic components as needed during assembly. The electronic components may be electrically connected to the wiring traces by soldering or other known techniques. During operation, electronic components typically generate significant excess heat energy that must be dissipated to maintain optimal performance.
[0019] The thermal interface provides a thermally conductive bridge between the electronic component and the heat sink, and may be thermally coupled to the thermal interface in a manner that most efficiently transfers thermal energy to the heat sink.
[0020] resin The thermally conductive composition of the present invention may include a non-silicone resin that provides a matrix for incorporating thermally conductive fillers and other additives. Examples of non-silicone resins useful in the composition of the present invention may include various thermoplastic materials, including thermoplastic elastomers that may or may not be inherently tacky. Suitable thermoplastic elastomers may include copolymers, including styrenic copolymers, such as styrene-butadiene-styrenestyrene (SBS), styrene-ethylene / butylene-styrene (SEBS), styrene-isoprene-styrene (SIS), styrene-ethylene / propylene-styrene (SEPS), and combinations thereof. Thermoplastic elastomers also include thermoplastic / elastomer blends and alloys, such as non-crosslinked polyolefins that are thermoplastic.
[0021] In some embodiments, the resin may include one or more of rubber, liquid, and wax hydrocarbon resins. Examples of hydrocarbon resins include saturated and unsaturated rubber compounds. Examples of saturated rubber compounds include ethylene propylene rubber, polyethylene / butylene, polyethylene-butylene-styrene, polyethylene-propylene-styrene, hydrogenated polyalkyldiene monol, hydrogenated polyalkyldiene diol, hydrogenated polyisoprene, and polyolefin elastomers.
[0022] In some embodiments, silyl-modified resins may be used in the matrix of the present invention. The resins are preferably non-silicone and the composition contains no more than trace amounts of silicone. In some embodiments, the composition does not contain silicone. The silyl-modified polymers may have a flexible backbone to reduce the modulus and glass transition temperature, such as polyether, polyester, polyurethane, polyacrylate, polyisoprene, polybutadiene, polystyrene butadiene, or polybutylene isoprene backbone.
[0023] In some embodiments, the resin may include one or more pressure-sensitive adhesives. The term "pressure-sensitive adhesive" or "PSA" as used herein refers to a viscoelastic material that adheres instantly to most substrates upon application of slight pressure and remains permanently tacky. A polymer is a PSA in the sense of the term as used herein if it has the properties of a PSA by itself or functions as a PSA by mixing with diluents and other additives. Examples of pressure-sensitive adhesives include block copolymers such as the styrene-based copolymers mentioned above, tackifying resins, and plasticizers. Pressure-sensitive adhesives may have certain rheological properties that are beneficial to the compositions of the present invention, including a combination of low softening point and low melt viscosity with high cohesive strength. The adhesive resin component may have low viscosity at low application temperatures and therefore be suitable for application methods in which the coating equipment contacts the substrate to be coated, such as in screen printing and engraved roll coating.
[0024] The resin may be present in the range of about 0.1 to about 50% by weight of the total composition. In some embodiments, the resin may be present in the range of about 0.5 to about 20% by weight of the total composition. In some embodiments, the resin may be present in the range of about 0.5 to about 10% by weight of the total composition. In some embodiments, the resin may be present in the range of about 0.5 to about 5% by weight of the total composition. In some embodiments, the resin may be present in the range of 1 to 3% by weight of the total composition.
[0025] Anti-oxidant phase change material The compositions of the present invention preferably include a phase change material that is phase changeable and has a melting point temperature or temperature range at or below the operating temperature or temperature range of an electronic component to which the thermally conductive material may be thermally coupled. The temperature activated phase change material changes from a solid state to a liquid state, and from a liquid state to a solid state, preferably within a temperature range of about 30° C. to about 160° C., more preferably 40° C. to 85° C. Phase change materials used in conventional compositions often include materials such as natural waxes, such as beeswax or carnauba wax, petroleum-based waxes, such as paraffin wax, or synthetic waxes, such as polyethylene glycols, polyethylenes, polyhydric alcohols, or chlorinated naphthalenes.
[0026] A typical conventional phase change material is a wax, such as paraffin wax, which has the general formula C n H 2n+2 and is a mixture of solid hydrocarbons having a melting point in the range of about 40° C. to about 140° C., more preferably in the range of 40° C. to 80° C. Examples of polymer waxes include polyethylene wax and polypropylene wax, and typically have a melting point in the range of about 40° C. to about 160° C.
[0027] As described herein, conventional phase change materials, such as waxes, tend to degrade at high temperatures commonly experienced in modern electronic packages. Applicants have discovered that by replacing some or all of the conventional phase change materials with low melting point secondary antioxidants, high performance phase change thermally conductive compositions can be achieved. Although secondary antioxidants have been used in thermal materials, the use of secondary antioxidants to enhance the phase change behavior of thermally conductive compositions is believed to be a new approach. It has been discovered that such low melting point secondary antioxidants can perform the phase change role in thermally conductive compositions while improving the high temperature reliability of such compositions.
[0028] In some embodiments, the phase change antioxidant component is a secondary antioxidant used in conjunction with a primary antioxidant and compatible with the primary antioxidant. Secondary antioxidants prevent the propagation of alkoxy and hydroxyl radicals and slow oxidation by decomposing hydroperoxides to produce non-reactive products. Primary antioxidants function by donating reactive hydrogen to the peroxy free radical to prevent subsequent free radical propagation. Antioxidant free radicals are stabilized by electron delocalization. In some embodiments, the secondary antioxidant is a thiol-based, such as a thioester. An example of a thiol-based secondary antioxidant is didodecyl 3,3'-thiodipropionate, which has a melting point temperature of 40-85°C. In some embodiments, the compatible primary antioxidant is a phenolic antioxidant. Phenolic antioxidants include simple phenols, bisphenols, polyphenols, and thiobisphenols.
[0029] It has been found that the concentration of the secondary antioxidant within the concentration range of the thermally conductive composition is important to maintain the functionality of the composition, particularly the relative concentration of the secondary antioxidant to the resin. Preferably, the secondary antioxidant is present in the composition at a concentration of 20-50% by weight of the non-silicone resin. The secondary antioxidant preferably has a melting point temperature of 40-85°C to function properly as a phase change component, although the secondary antioxidant more preferably has a melting point temperature of 50-60°C.
[0030] The secondary antioxidant may be present in the composition in a ratio of 95-99 parts by weight secondary antioxidant to 1-5 parts by weight primary antioxidant. In some embodiments, the secondary antioxidant may be present in the composition in a ratio of 97-99 parts by weight secondary antioxidant to 1-3 parts by weight primary antioxidant.
[0031] In some embodiments, the thermally conductive composition of the present invention is substantially free of a wax component. However, in other embodiments, the thermally conductive composition includes a wax component. In some embodiments, the wax component is a hydrocarbon wax. In some embodiments, the hydrocarbon wax has a melting point temperature of 40-120° C. In some embodiments, the hydrocarbon wax has a melting point temperature of 40-80° C. In some embodiments, the hydrocarbon wax is a paraffin wax.
[0032] Thermally Conductive Particles To achieve the desired low thermal impedance of the thermally conductive interface, the composition of the present invention includes thermally conductive particles dispersed therein. The particles may be both thermally conductive and electrically conductive. Alternatively, the particles may be thermally conductive and electrically insulating. A variety of thermally conductive particles may be useful in the composition of the present invention. However, it has been found that thermally conductive particles selected from aluminum, aluminum nitride, aluminum silica alloy, zinc oxide, and combinations thereof are most useful in the composition of the present invention.
[0033] The particulate filler material may be a granular powder, whiskers, fibers, or other suitable shape. The particles may be substantially spherical, platelet-like, rod-like, or combinations thereof. In some embodiments, the thermally conductive particles may have a particle size of less than 25 μm. Here, the term "particle size" refers to the particle diameter or effective particle diameter. In some embodiments, the thermally conductive particles may have a particle size of 0.01 to 25 μm. In some embodiments, the thermally conductive particles may be monodisperse.
[0034] In some embodiments, the thermally conductive particles, which may include one or more material types, may have a particle size distribution with particle sizes ranging from 0.01 to 25 μm.
[0035] In some embodiments, the particle size distribution may be multimodal having a plurality of concentration peaks of particle sizes between 0.01 and 25 μm. In some embodiments, a first concentration peak of the multimodal distribution is between 0.1 and 3 μm in size, and a second concentration peak of the multimodal distribution is between 8 and 12 μm in size. The first concentration peak of the multimodal distribution may comprise 10-90% by weight of the total thermally conductive filler; in some embodiments, the first concentration peak of the multimodal distribution may comprise 15-80% by weight of the total thermally conductive filler; in some embodiments, the first concentration peak of the multimodal distribution may comprise 15-50% by weight of the total thermally conductive filler; in some embodiments, the first concentration peak of the multimodal distribution may comprise 15-30% by weight of the total thermally conductive filler. The second concentration peak of the multimodal distribution may comprise 10-90% by weight of the total thermally conductive filler; in some embodiments, the second concentration peak of the multimodal distribution may comprise 15-80% by weight of the total thermally conductive filler; in some embodiments, the second concentration peak of the multimodal distribution may comprise 25-60% by weight of the total thermally conductive filler. A multimodal distribution may include two or more concentration peaks of particle size.
[0036] In some embodiments, the thermally conductive particulate filler may comprise a trimodal particle size distribution with particle sizes between 0.01 and 25 μm. A first concentration peak of the trimodal distribution is the particle size of aluminum nitride between 0.1 and 3 μm, a second concentration peak of the trimodal distribution is the particle size of aluminum or aluminum-silica alloy (silica stabilized aluminum) between 8 and 12 μm, and a third concentration peak of the trimodal distribution is the particle size of zinc oxide between 0.01 and 0.5 μm. The first concentration peak of the trimodal distribution comprises 15-35% by weight of the total thermally conductive filler. The second concentration peak comprises 25-60% by weight of the total thermally conductive filler. The third concentration peak comprises 15-35% by weight of the total thermally conductive filler.
[0037] The thermally conductive particulate filler may comprise at least 25 wt.% aluminium and / or aluminium-silica alloy particles, preferably at least 35 wt.% aluminium and / or aluminium-silica alloy particles, more preferably at least 40 wt.% aluminium and / or aluminium-silica alloy particles.
[0038] In some embodiments, the particle size is the average particle size (d 50 ) may be represented as
[0039] The thermally conductive particulate filler may be dispersed in the resin and present in the composition at a loading level of 20-98% by weight of the total composition. In some embodiments, the thermally conductive particulate filler comprises 40-97% by weight of the total composition. In some embodiments, the thermally conductive particulate filler comprises 50-95% by weight of the total composition. Desirably, sufficient thermally conductive particles are provided such that a thermally conductive interface formed from the composition exhibits a thermal conductivity of at least 0.5 W / m·K, preferably at least 1 W / m·K, and more preferably at least 2 W / m·K.
[0040] Plasticizer The thermally conductive composition of the present invention may include a plasticizer component to adjust the viscosity of the dispersible mass, especially under shear, and to maintain the solid state and melt viscosity within a desired range. Plasticizers useful in the compositions of the present invention are those that are effective in promoting the flowability of the agglomerates that make up the composition. The plasticizers used in the compositions of the present invention may preferably be low volatility liquids that reduce the viscosity of the composition. In some embodiments, the plasticizer may exhibit a viscosity of less than 1000 cP at 25° C. In another embodiment, the plasticizer may exhibit a viscosity of less than 500 cP at 25° C. In a further embodiment, the plasticizer may exhibit a viscosity of less than 100 cP at 25° C.
[0041] In some embodiments, the plasticizer may comprise from about 0.1 to about 25% by weight of the composition. In some embodiments, the plasticizer may comprise from about 0.5 to about 10% by weight of the composition. In some embodiments, the plasticizer may comprise from about 0.5 to about 5% by weight of the composition. The plasticizer may preferably be present at less than 20% by weight of the composition.
[0042] Examples of plasticizers include sebacates, adipates, terephthalates, dibenzoates, gluterates, phthalates, azelates, benzoates, sulfonamides, organic phosphates, glycols, polyethers, trimellitates, polybutadienes, epoxies, amines, acrylates, thiols, polyols, and isocyanates. A preferred plasticizer is trimellitate.
[0043] Supplemental Antioxidants In addition to the primary and secondary antioxidants described above, the compositions of the present invention may include additional antioxidant components that are functionally complementary to the primary and secondary antioxidants, but different from the primary and secondary antioxidants described above. In some embodiments, the compositions of the present invention may include one or more supplementary primary and secondary antioxidants that are different from the primary and secondary antioxidants described above. Exemplary supplementary antioxidants include hindered phenols and secondary aromatic amines. An example of a sterically hindered phenol useful as a supplementary antioxidant in the compositions of the present invention is Irganox® 1010 from BASF. Metal deactivating antioxidants may also be used in the compositions of the present invention, an example of which is Irganox® MD1024 from BASF.
[0044] In some embodiments, the thermally conductive compositions of the present invention may include one or more supplemental antioxidants at a concentration of 0.01 to 10% by weight of the composition. In some embodiments, the thermally conductive compositions of the present invention may include one or more supplemental antioxidants at a concentration of 0.05 to 5% by weight of the composition. In some embodiments, the thermally conductive compositions of the present invention may include one or more supplemental antioxidants at a concentration of 0.1 to 3% by weight of the composition.
[0045] Optional Additives According to some embodiments of the present invention, the compositions described herein may further comprise one or more additives, such as stabilizers, dispersants, colorants, adhesives, wetting agents, flame retardants, extenders, and corrosion inhibitors.
[0046] Thermal Conductive Compound Properties In a preferred embodiment, the thermally conductive composition exhibits a thermal conductivity of at least 0.5 W / m·K, preferably at least 1 W / m·K, more preferably at least 2 W / m·K. Additionally, the thermally conductive composition exhibits high temperature stability, exhibiting less than 20% weight loss after 1000 hours at 175° C., preferably less than 10% weight loss after 1000 hours at 175° C. The thermally conductive composition preferably exhibits less than 10% degradation in thermal performance, such as thermal conductivity or thermal impedance, after 1000 hours at 175° C., more preferably less than 5% degradation in thermal performance after 1000 hours at 175° C.
[0047] Goods The thermally conductive composition of the present invention may be used to manufacture articles of various shapes. The article may be used as an interface between a heat generating device and a heat dissipating device. The heat generating device transfers heat to the interface article, causing the interface article to melt at an operating temperature below 120°C, often below 85°C. When the phase change material melts, a liquid film is formed at the interface surface of the interface article, the electronic component, and the heat dissipator. The film containing the phase change material reduces the thermal resistance of the interface surface. The resin matrix of the thermally conductive interface provides a network to contain the liquid phase change material and prevents it from flowing out of the interface.
[0048] The composition may be melt extruded into a thin film. In contrast, conventional films made from silicone-based filler compositions are generally much thicker. In certain applications, non-silicone resin films have been found to be more advantageous than silicone versions. For example, thin silicone films tend to have poor handling properties and may require support structures to maintain their integrity. In addition, silicone resins and particulate filler materials may be incompatible due to different densities and the low viscosity of silicone resins. Therefore, the composition of the present invention is preferably non-silicone.
[0049] printable composition In some embodiments, the thermally conductive compositions of the present invention may be printable by conventional printing devices such as inkjet printers, fused filament printers, and other three-dimensional printers. In some embodiments, the compositions of the present invention may be melt extruded through a print head or die. In other embodiments, the compositions of the present invention may be dissolved or suspended in a solvent suspension and then dispensed through a suitable nozzle or slot. Solvent-based printing may be performed by printing a solution or suspension / dispersion onto a substrate, followed by drying the solvent at room temperature or above and / or under reduced pressure. Although a variety of solvents are believed to be useful for this purpose, acetate-based solvents such as ethyl acetate and ethylhexyl acetate are suitable solvents. EXAMPLES
[0050] The following compositions were prepared and demonstrate the thermally conductive composition properties described herein.
[0051] Example 1: Material Weight% Thermoplastic resin 1~10 Primary antioxidant 0.05~0.2 Secondary antioxidant / phase change material 0.5~5 (Didodecyl 3,3'-thiodipropionate) Trimellitate plasticizer 0.5~5 Wetting agent 0.2~2 Zinc oxide 20~30 Aluminum nitride 20~30 Aluminum-silica alloy 40~50 Supplementary Antioxidants 0.1~1
[0052] Example 2: Material Weight% Thermoplastic resin 1~10 Primary antioxidant 0.05~2 Secondary antioxidant / phase change material 0.5~5 (Didodecyl 3,3'-thiodipropionate) Trimellitate plasticizer 0.5~5 Wetting agent 0.2~2 Zinc oxide 18~26 Aluminum nitride 18~26 Aluminum-silica alloy 35~45 Supplementary Antioxidants 0.1~1 Solvent 5~15
Claims
1. 0.5 to 20 wt. % of a non-silicone resin; Primary antioxidants; a thiol-based secondary antioxidant that is compatible with the primary antioxidant and is present in the composition at a concentration of 20 to 50 weight percent of the non-silicone resin, the secondary antioxidant being present in the composition in a ratio of 95 to 99 weight percent of the secondary antioxidant to 1 to 5 weight percent of the primary antioxidant, the secondary antioxidant having a melting point temperature of 40 to 85° C.; and 50-98 wt. % of a thermally conductive particulate filler; A thermally conductive composition comprising: A thermally conductive composition exhibiting a thermal conductivity of at least 1 W / m·K and exhibiting less than 20% weight loss after 1000 hours at 175°C.
2. The thermally conductive composition of claim 1 , wherein the non-silicone resin comprises a pressure sensitive adhesive.
3. 2. The thermally conductive composition of claim 1, comprising 0.5 to 5 weight percent of the non-silicone resin.
4. The thermally conductive composition of claim 3 , wherein the non-silicone resin comprises a polyamide.
5. The thermally conductive composition of claim 1 comprising a hydrocarbon wax having a melting point temperature of 40 to 120°C.
6. The thermally conductive composition of claim 1 , wherein the composition is substantially free of wax.
7. The thermally conductive composition according to claim 1, wherein the secondary oxidizer has a melting point temperature of 50 to 60°C.
8. 10. The thermally conductive composition of claim 1, wherein the secondary antioxidant comprises dodecylthiopropionate.
9. 10. The thermally conductive composition of claim 1, wherein the thermally conductive particulate filler is selected from aluminum, aluminum nitride, aluminum-silica alloy, zinc oxide, and combinations thereof.
10. The thermally conductive particulate filler has an average particle diameter (d 50 10. The thermally conductive composition of claim 9, having a molecular weight of 1000 to 15000.
11. The thermally conductive composition of claim 10, comprising 70 to 95 weight percent of said thermally conductive particulate filler.
12. 10. The thermally conductive composition of claim 1, comprising 0.5 to 20 weight percent trimellitate plasticizer.
13. The thermally conductive composition of claim 12 comprising 0.5 to 5 weight percent of said trimellitate plasticizer.
14. The thermally conductive composition of claim 13, comprising 0.1 to 1.5 weight percent of a wetting agent.
15. 15. The thermally conductive composition of claim 14, comprising 0.1 to 1.5 weight percent of a sterically hindered phenolic antioxidant different from said primary antioxidant and said secondary antioxidant.
16. 16. The thermally conductive composition of claim 15, comprising 0.1 to 1.5 weight percent of a metal deactivating antioxidant different from said primary antioxidant and said secondary antioxidant.
17. A thermally conductive printable composition comprising the thermally conductive composition of claim 1 dissolved in a compatible solvent.
18. 18. The thermally conductive printable composition of claim 17, wherein the solvent is selected from ethyl acetate and ethylhexyl acetate.